UniCrime: A mobile solution for on campus crime reporting using volunteered geographic information - Ariffin I.; Hanif M.F.M.; Solemon B. (Science and Engineering Institute, 2023)
Crime; Disaster prevention; Mobile computing; Mobile telecommunication systems; Surveys; Alternative source; Geographic information; Health monitoring; Information sources; Mobile applications; Mobile solutions; Telecommunication technologies; Volunteered geographic information; Software prototyping